Evolution and current scenario of irrigated area in Brazil: Systematic data analysis - Daniel F. de Carvalho; Rosária da C. F. Martins; Jaqueline J. S. dos Santos; Gean C. Teles; Marcello A. D. Gentile; Marcelo S. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Water is an essential element to life and used in various human activities. However, because of the amount used in agriculture and the increase in irrigated area, the sustainable use of this resource has become a worldwide concern. In this study, data from the Censuses of Agriculture published by the Instituto Brasileiro de Geografia e Estatística (IBGE) from 1960 to 2017 were evaluated in relation to the regions and irrigation methods, performing a detailed analysis between the data from the 2006 and 2017 Censuses. There was an increase in irrigated area in Brazil in all geographic regions, reaching 6.9 million hectares in 2017. Sprinkler irrigation methods are the most used, with 48% of the irrigated area, followed by localized irrigation (24.4%) and surface irrigation (22.3%). Drip irrigation is the most used system in establishments up to 50 ha (617,423 ha), followed by conventional sprinkler (514,893 ha), while the center pivot stands out in areas larger than 50 ha (1,362,828 ha). The Southeast region (38.6%) and the states of Rio Grande do Sul (20.4%), Minas Gerais (16.6%) and São Paulo (16.0%) stand out as the ones with the largest irrigated area in the country. The State of Minas Gerais showed the highest growth of irrigated area in the 2006-2017 period (116.1%), due to the expansion of areas irrigated with center pivot.